Computer Music and Digital Media Art Through a Web-Based Collaborative Interface - Luís Henrique Pinto Arandas (2019)
The dissertation presented is the result of an investigation into collaborative interfaces using web technologies, done in the context of Braga Media Arts. As a result an audiovisual environment is presented as a practical development, Akson. Akson was initially conceived of as an exploration into what could be built by leveraging global internet infrastructure as well as musical and visual playback across multiple devices. This system was done thinking about its use in live performance and is able to interact with the devices of the public.